Two new species of Medetera Fischer von Waldheim (Diptera, Dolichopodidae) from Russia and Mongolia - Negrobov, Oleg P.; Naglis, Stefan (Zootaxa, 2015)
Two new species Medetera sakhalinensis Negrobov & Naglis sp. nov. from Russian Far East (Sakhalin) and M. emeljanovi Negrobov & Naglis sp. nov. from Mongolia are described and differential diagnosis are given.